인용 · 피인용 구절을 이용한 다주제 인용 분석 서비스 방법 연구 - 정한민(Hanmin Jung); 김태홍(Taehong Kim) (한국콘텐츠학회 논문지, 21(10), 2021)
The analysis of citing and cited phrases provides an opportunity to enhance search-centric academic information services. However, most current studies focus only on citation analysis among academic associations, researchers, and articles, making it challenging to develop higher citation-based information services. This study proposes citation analysis service methods using citing and cited phrases. First, to verify the feasibility of suggested services, we have collected the most highly cited articles with specific domain terms and followed their citing relationship; after that, we found formal citation types and ratios in the original articles. And we conducted structural analysis, especially with three topics, "Deep Learning," "Green Energy," and "Aging," and then structurally illustrates the citation characteristics of related articles. Finally, we collected four most cited articles and all their citing ones for each subject from Google Scholar and analyzed the ratio of citation types and citation spread. We hope that various citation analysis studies and information services can be further developed based on our discussion for designing better information services. 인용 및 피인용 구절 분석은 정보 검색 위주의 단순 학술정보 서비스를 고도화시킬 기회를 제공한다. 그렇지만, 대부분의 연구가 커뮤니티, 연구자, 논문 간 인용 지수 중심의 분석에 초점을 맞추고 있어, 인용 구절 분석에 기반한 인용 기반 논문 정보 서비스를 제공하기에는 어려움이 있다. 본 연구는 "딥러닝", "그린에너지", "노령화"라는 세 개의 주제를 대상으로 논문 내 인용 구절 분석을 수행하고, 피인용 논문의 인용 특성을 구조적으로 설명한다. 이를 위해 구글 스칼라를 통해 각 주제에서 가장 많이 인용된 피인용 논문 각 네 편과 모든 인용 논문들을 수집하였으며, 이들을 대상으로 인용 유형 비율 분석과 인용 확산 분석을 수행하는 방식으로 피인용 논문 특성을 파악하고, 정보 서비스에 어떻게 반영할 수 있는지를 논하였다. 본 연구를 기반으로 다양한 인용 분석 연구와 정보 서비스가 개발될 수 있기를 기대한다.